Intergroup Contact and Outgroup Humanization: Is the Causal Relationship Uni- or Bidirectional? - Capozza, Dora (PLoS One, 2017)
The attribution of uniquely human characteristics to the outgroup may favor the search for contact with outgroup members and, vice versa, contact experiences may improve humanity attributions to the outgroup. To explore this bidirectional relationship, two studies were performed. In Study 1, humanity perceptions were manipulated using subliminal conditioning. Two experimental conditions were created. In the humanization condition, the unconditioned stimuli (US) were uniquely human words; in the dehumanization condition, the US were non-uniquely human and animal words. In both conditions, conditioned stimuli were typical outgroup faces. An approach/avoidance technique (the manikin task) was used to measure the willingness to have contact with outgroup members. Findings showed that in the humanization condition participants were faster in approaching than in avoiding outgroup members: closeness to the outgroup was preferred to distance. Latencies of approach and avoidance movements were not different in the dehumanization condition. In Study 2, contact was manipulated using the manikin task. One approach (contact) condition and two control conditions were created. The attribution of uniquely human traits to the outgroup was stronger in the contact than in the no-contact conditions. Furthermore, the effect of contact on humanity attributions was mediated by increased trust toward the outgroup. Thus, findings demonstrate the bidirectionality of the relationship between contact and humanity attributions. Practical implications of findings are discussed.